Penguatan Ekonomi Masyarakat Desa Jatiendah melalui Pendampingan Sertifikasi Halal UMKM dan Literasi Koperasi Merah Putih - Novia Astuti Dewi; Muhammad Daffa Rifki Ananda; Maura Malika Syabillah; Aulia Nur Fathia; Tasya Khopipah Almeisya; Muhammad Akmal Dzakwan; Muhammad Satria Dimas; Gery Gery; Ikhsan Tyo Dewanggara; Dicky Mauludi (Jurnal Pengabdian kepada Masyarakat Indonesia (JPKMI), 2025)
Strengthening the village economy is a strategic step in fostering local independence and competitiveness. One of the challenges faced by MSMEs in Jatiendah Village is the limited knowledge of halal certification, which has become mandatory under Law Number 33 of 2014 on Halal Product Assurance. In addition, community members still have low cooperative literacy, even though cooperatives play an important role as people's economic institutions. This community service activity aims to improve MSME actors’ understanding of the halal certification process and strengthen community literacy regarding the functions of cooperatives. The methods used were counseling, socialization, and technical assistance with a participatory approach. The results showed an increase in participants' understanding, indicated by active discussions and positive responses to the importance of halal certification and the use of cooperatives as a means of strengthening the local economy. This program is expected to support the sustainability of MSMEs while optimizing the role of cooperatives as drivers of the village economy.